The therapeutic potential of stem cells in Alzheimer's Disease (Research, Society and Development, 2023)
Stem cells are known for their high ability to regenerate and differentiate in different body tissues, and they are divided into four types: embryonic, neural, induced pluripotent and mesenchymal. From this, it is possible to analyze the therapeutic potential of these cell types in neurodegenerative diseases, more specifically, Alzheimer's Disease (AD). Thus, an integrative review was conducted with the objectives of describing the contribution and main methods of stem cell use in the treatment of Alzheimer's disease currently tested and used, as well as discussing their efficacy and feasibility. In this context, with the expected aging of the population, this pathology tends to affect a large part of the world’s citizens. In AD, the therapeutic action of these cells may be, mainly, to reduce its pathophysiological effects. This happens through biochemical mechanisms which have as a promising prognosis the reduction of cognitive and memory dysfunctions, according to tests performed in mice. Therefore, from the analysis of these studies and tests, it was possible to recognize the importance of improving and directing these researches towards Alzheimer's Disease, one of the main causes of dementia, according to both the pathophysiological mechanisms of this illness, as well as the advantages and disadvantages of each type of stem cell.